Ethnic-cultural procedural fairness effects on organizational identification and job satisfaction among minority and majority employees - Kim Dierckx; Hilde Depauw; Tessa Haesevoets; Barbara Valcke; Thomas Van Roey; Bart Van de Putte; David De Cremer; Crizelle Els; Alain Van Hiel (Frontiers in Psychology)
In the present contribution, we examined the application of procedural fairness in the resolution of ethnic-cultural (EC) issues, which are issues relating to ethnic, cultural, and linguistic matters. We hypothesized that EC procedural fairness perceptions contribute to effective diversity management because they are positively related to job satisfaction among minority group employees. We further theorized that this relationship is mediated by organizational identification. What makes the present study particularly unique is that we employ a dual focus, by examining the perceptions of both minority and majority group members. Two field studies (total N = 2,059; 26.3% minority members) and a longitudinal field survey (N = 265 minority members) supported our predictions. In Study 1, we consistently found that minority employees’ EC procedural fairness perceptions were positively associated with job satisfaction. Moreover, organizational identification fully mediated this relationship. Interestingly, similar positive responses to EC procedural fairness were observed among majority group employees. Study 2 sampled minority employees working in various countries and industrial sectors on two different measurement occasions. Multilevel mediation analyses provided further support for the mediating role of organizational identification. Finally, Study 3 sampled minority and majority group assembly line workers pertaining to various ethnically diverse teams. In line with Study 1, our multilevel analyses revealed that EC procedural fairness perceptions were related to enhanced job satisfaction (through organizational identification) among minority and majority group employees. Taken together, the present results highlight that procedural fairness can be implemented to resolve ethnic-cultural issues in today’s super-diverse organizations, and by doing so, they emphasize the potential of procedural fairness for organizational diversity management.